Serotype Characterization of Streptococcus pneumoniae Identified in Meningitis Cases in Sevral Asian and European Countries - A. N. Oganesyan; E. A. Voropaeva; A. A. Mel'nikova; Yu. N. Urban; E. A. Egorova; V. A. Aleshkin (Эпидемиология и вакцинопрофилактика)
Background. The current epidemiology of pneumococcal meningitis in Ukraine, Georgia and countries of CIS is poorly studied. In order to ensure an effective vaccination strategy and post-vaccination surveillance, we examined the serotype distribution patterns of pneumococcal meningitis in the following regions: European (Ukraine, Belarus), Transcaucasian (Azerbaijan, Armenia, Georgia), and Asian (Uzbekistan, Kyrgyzstan, Kazakhstan). The study was performed within the program for Invasive Bacterial Diseases Sentinel Surveillance implemented in the region by WHO Regional Office for Europe. Methods. Cerebrospinal fluid (CSFs) samples were collected from patients with suspected meningitis at sentinel hospitals throughout all the regions within the period 2007 - 2016. Determination of S. pneumoniae and serogroups/serotypes in positive CSFs was performed using qPCR and mPCR. In total 3013 CSFs were tested: 2764 (91.7%) of them were collected from patients aged under 5 years, 128 (4.2%) from children aged 5 - 18 years and 121 (4.1%) from adults. Results. 6% (188) of CSFs analyzed were positive for S. pneumoniae, The PCR assay used could predict the S. pneumoniae serotypes/ serogroups for 82% (n = 154) of positive CSFs, 16% were not-typeable in our PCR scheme and for 2% serotyping was not performed. In total, 26 different serotypes/serogroups were identified. Serotypes 6A/B (21%), 14 (15%), 19F (10%), 23F (7%), 18 (A/B/C) (4%), 9V/9A (3%) and 4 (3%) were found to be the most prevalent, followed by others with a prevalence of 2% and less(6C/6D, 24(A/B/F), 19A, 5, 3,1,23A,20,2,13,31, 8, 7F/7A, 7C/7B/40, 22F/22A, 21, 15B/15C, 12F/12A/12B/44/46, 11A/11D). Conclusions. The proportion of vaccine serotypes in pneumococcal meningitis cases (vaccine coverage) amounts to 67% for PCV10 and 71% for PCV13 in all the regions, suggesting that the introduction of conjugate vaccines (PCV10 and 13) into National Immunization Programs is feasible. Post-vaccine introduction surveillance supported will be essential. Post-vaccine introduction surveillance and monitoring of changes in serotype S. pneumoniae distribution in cases with invasive pneumococcal disease and in healthy carriers is essential to assess the vaccination effectiveness and to provide a comprehensive picture of the vaccination impact on pneumococcal serotype distribution in the region.